Knowledge and attitudes of welfare entrepreneurs about welfare technology – a survey for South Ostrobothnian entrepreneurs - Toivonen, Marika; Vainionpää, Jaana (Finnish Journal of eHealth and eWelfare, 2020)
In Finland, digitalization and utilization of technology and mobile service solutions are topical issues in various programs and goals of the Government and Ministries. Current economic situation paired with the current population forecast in addition with the changing work life in a global perspective, challenge the ways work is currently performed. However, in welfare services there is still limited utilization of technology. This is due to the varying degrees of utilization of technology between companies, undeveloped ecosystems and the challenge to prove the efficiency and cost-benefit of using technology in welfare services. In this article, we discuss welfare entrepreneurs’ beliefs, current knowledge and need for information about welfare robotics and different mHealth solutions and solutions using artificial intelligence (AI). The data was collected during spring 2019 using an electronic survey. The survey was directed to entrepreneurs and managing directors of welfare companies, whose head office is located in the region of South Ostrobothnia, Finland. The survey revealed that the South Ostrobothnian entrepreneurs and managing directors experienced their knowledge on welfare-technology low and there appeared to be a need for additional information on various fields. Lack of knowledge and therefore a need for information was especially experienced in the co-operation between humans and robots and the impacts of mHealth and AI-solutions. A majority of respondents told that their attitudes towards welfare technology is fairly negative. The advantage technology would bring was named as being the reduction of human work load. The major challenge was seen to be the lack or decrease of human touch and interaction and the possible decrease in positions. The number of respondents remained low (n=6). Therefore, the results cannot be generalized. Nonetheless, the results verify the impression about knowledge and attitudes towards health care technology. The ones who did not answer the questionnaire might even have less interest and less knowledge than the ones who did answer the questionnaire.